„Ne, das kann ich besser!“: Motive und Bedeutung der Contemporary TV Drama Serie The Mentalist für FanfictionautorInnen - Goldmann, Julia Elena (Global Media Journal - German Edition, 2015)
Loners and outsiders, who can be distinguished through excessive consumption of and the knowledge of trivia around a specific cultural product as well as obsessive consumerism of said product – even today the image of fans is a highly stereotyped one. Usually, the reputation of a dedicated fan is not associated with an active, creative producer of cultural capital. In reality, most of them are though – a fact that can easily be shown by a single Google search. This article focuses one form of such fan-productivity: the creation of fan fiction. Fan fictions are user-generated, fictional stories which feature characters of the preferred, popular cultural fan object – here: the The Mentalist-series – and are nowadays posted on appropriate websites. To be more precise, this paper focuses conditions of and motivations for the production of German fan fiction and the consequent publication of said stories on the website www.fanfiktion.de of five authors. It will be underlined that all authors approach the production of fan fiction in a highly organized way even though their stories themselves show a great variety. Furthermore, the importance of fan fiction reviews and comments is essential for all five authors, whose age varies from 13 to 53 years.